Possible Association between Behçet's Disease and Periodontal diseases - Fikriye Orduyilmaz; Nurdan Ozmeric; Serenay Elgun; Sühan Gürbüz; Hamit Kucuk; Berivan Bitik; Abdurrahman Tufan; Berna Göker (BMC, 2024)
Abstract Aim This study explores the connection between Behçet's disease (BD), characterized by persistent oral and genital ulcers alongside iritis, and periodontal disease. It examines the levels of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and nitric oxide (NO) in gingival crevicular fluid (GCF) and saliva. Methods Forty Behçet's patients with gingivitis or periodontitis and 47 patients with either gingivitis or periodontitis but without BD were studied. Periodontal status was recorded with standard clinical indexes. GCF and saliva samples were obtained. NO, IL-1β and TNF-α levels were analysed. Current Behçet's symptoms and medications usage were recorded. Results Mean salivary IL-1β was elevated (p = .045), and mean NO level was decreased in BD patients with gingivitis compared to patients without BD (p = .000). In contrast, mean NO level in crevicular fluid was higher in Behçet's patients with periodontitis than in patients without BD (p = .009). Furthermore, among Behçet's patients, those with vascular involvement had lower salivary NO level compared to patients without vascular involvement (p = .000). Conclusions Based on our findings, the elevated levels of IL-1β in the saliva of Behçet's patients with gingivitis, along with the decreased NO level, indicate an altered inflammatory response in the oral cavity.